Potentiation of GABAergic synaptic transmission by diazepam acutely increases resting beat-to-beat blood pressure variability in young adults - Teixeira, André L; Nardone, Massimo; Samora, Milena; Fernandes, Igor A; Ramos, Plinio S; Sabino-Carvalho, Jeann L; Ricardo, Djalma R; Millar, Philip J; Vianna, Lauro C (The FASEB journal, 2022)
Resting beat-to-beat blood pressure (BP) variability is a powerful predictor of cardiovascular events and end-organ damage. Recent studies indicate that resting beat-to-beat BP variability possesses greater prognostic value when compared with traditional 24-h ambulatory or home-based BP monitoring. However, despite the well-recognized clinical significance of resting beat-to-beat BP variability, its underlying mechanisms remain incompletely understood. The sympathetic nervous system is critical for BP regulation. Given that the sympathetic pre-motor neurons are highly regulated by inhibitory GABAergic interneurons, it is reasonable to speculate that GABA receptors may contribute to the beat-to-beat BP variability. However, this hypothesis has not been tested experimentally before. Therefore, in this study, we tested the hypothesis that a potentiation of GABAergic synaptic transmission by diazepam would acutely increase resting beat-to-beat blood pressure variability in humans. In 40 (17 females) young, normotensive adults, resting beat-to-beat BP (finger photoplethysmography) was continuously measured for 5-10 min, 60 min after the oral administration of either diazepam (10 mg) or placebo. The experiments were conducted in a randomized, double-blinded, placebo-controlled and crossover design. Stroke volume was estimated from the BP waveform (ModelFlow) permitting the calculation of cardiac output (CO) and total peripheral resistance (TPR). Parameters of variability included the standard deviation, range, interquartile range (the difference between the 25th and 75th percentiles within-subject), the coefficient of variation [(SD/mean) x 100], and the average real variability. Additionally, direct recordings of muscle sympathetic nerve activity (MSNA, microneurography) were obtained in a subset of subjects (n=13) and the gain of arterial baroreflex control of MSNA (sympathetic baroreflex) and heart rate (cardiac baroreflex), as well as signal-averaged sympathetic transduction of blood pressure calculated. Compared to placebo, diazepam significantly increased the standard deviation of systolic (4.7 ± 1.4 vs. 5.7 ± 1.5 mmHg, P = 0.001), diastolic (3.8 ± 1.2 vs. 4.5 ± 1.2 mmHg, P = 0.007) and mean BP (3.8 ± 1.1 vs. 4.5 ± 1.1 mmHg, P = 0.002), as well as CO (469 ± 149 vs. 626 ± 259 ml/min, P < 0.001) and TPR (1.0 ± 0.3 vs. 1.4 ± 0.6 mmHg/l/min, P < 0.001). Similar results were found using all indices of variability. Furthermore, diazepam reduced resting MSNA burst frequency (placebo: 22 ± 6 bursts/min vs. diazepam: 18 ± 8 bursts/min, P = 0.025) without affecting cardiac or sympathetic baroreflex sensitivity. However, the peak increase in mean BP following a spontaneous burst of MSNA (i.e., sympathetic transduction) was accentuated after diazepam administration. This is the first study to indicate that GABA receptors may play a role in resting beat-to-beat BP variability. These findings advance our current understanding of the neural network mechanisms contributing to the resting beat-to-beat BP variability in young adults.